Another person's poison : a history of food allergy - Smith, Matthew, 1973- (Arts and traditions of the table., 2015)
For most of the 20th century, food allergies were considered a fad or junk science. While many physicians and clinicians argued that certain foods could cause a range of chronic problems, from asthma and eczema to migraines and hyperactivity, others believed that allergies were psychosomatic. This book traces the trajectory of this debate and its effect on public-health policy and the production, manufacture, and consumption of food.